A Cost-Effectiveness Analysis of Systemic Therapy for Metastatic Hormone-Sensitive Prostate Cancer - Sung, Winnie W. Y.; Choi, Horace C. W.; Luk, Peter H. Y.; So, Tsz Him (Frontiers in Oncology, 2021)
Background: Currently, approved first-line treatment options of metastatic hormone-sensitive prostate cancer (mHSPC) include (1) androgen deprivation therapy (ADT) alone, ADT plus one of the following: (2) docetaxel, (3) abiraterone, (4) enzalutamide, and (5) apalutamide. The high cost of novel androgen receptor pathway inhibitors warrants an understanding of the combinations’ value by considering both efficacy and cost. Objective: This study aimed to compare the cost-effectiveness of these five treatment options in mHSPC from the US payer perspective to guide treatment sequence. Methods: A Markov model was developed to compare the lifetime cost and effectiveness of these five first-line treatment options for mHSPC using outcomes data from published literature. Health outcomes were measured in life-years and quality-adjusted life-years (QALYs). Drug costs were obtained from the Veterans Affairs Pharmaceutical Catalog. We extrapolated survival beyond closure of the trials. Outcome Measurements and Statistical Analysis: Life-years, QALYs, lifetime costs and incremental cost-effectiveness ratios (ICERs) were estimated. Univariable, 2-way, and probabilistic sensitivity analyses were performed to evaluate parameter uncertainty. A willingness-to-pay (WTP) threshold of US$100,000 per QALY was used. Results: Compared to ADT alone, docetaxel plus ADT provided a 0.31 QALY gain at an ICER of US$1,542 per QALY. Abiraterone plus ADT provided an additional 1.29 QALYs against docetaxel plus ADT, with an ICER of US$26,416 per QALY. Compared to abiraterone plus ADT, enzalutamide plus ADT provided an additional 0.06 QALYs at an ICER of US$3,826,216 per QALY. Apalutamide plus ADT was strongly dominated by abiraterone plus ADT. Given the WTP threshold of US$100,000 per QALY, abiraterone plus ADT represented high-value health care. Conclusions: Abiraterone plus ADT is the preferred treatment option for men with mHSPC at a WTP threshold of US$100,000 per QALY.